2024
DOI: 10.1021/acs.jafc.4c02123
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulation of SugarCane Response to Sporisorium scitamineum: Insights from Time-Course Gene Coexpression and Ca2+ Signaling

Qibin Wu,
Chang Zhang,
Fu Xu
et al.

Abstract: Sugarcane response to Sporisorium scitamineum is determined by multiple major genes and numerous microeffector genes. Here, time-ordered gene coexpression networks were applied to explore the interaction between sugarcane and S. scitamineum. Totally, 2459 differentially expressed genes were identified and divided into 10 levels, and several stress-related subnetworks were established. Interestingly, the Ca 2+ signaling pathway was activated to establish the response to sugarcane smut disease. Accordingly, two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…Our previous study showed that the sugarcane ScCAX4 gene was induced post Sporisorium scitanmineum infection . Besides, transient overexpression of the sugarcane ScCAX2/3 genes in Nicotiana benthamiana resulted in the compromised resistance of the plant to pathogen infection . However, the molecular mechanism of how CAX genes regulate the plant response to pathogen stress remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study showed that the sugarcane ScCAX4 gene was induced post Sporisorium scitanmineum infection . Besides, transient overexpression of the sugarcane ScCAX2/3 genes in Nicotiana benthamiana resulted in the compromised resistance of the plant to pathogen infection . However, the molecular mechanism of how CAX genes regulate the plant response to pathogen stress remains unclear.…”
Section: Introductionmentioning
confidence: 99%